AKUNTABILITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH DALAM PEMBANGUNAN INFRASTRUKTUR DAERAH KABUPATEN HALMAHERA UTARA - GOHORA, JONI; LENGKONG, FLORENCE DAICY; PLANGITEN, NOVVA (Sam Ratulangi University, 2017)
The local government as a stakeholder in the area should be responsible for the implementation of the development so thatcreated equitable development and the process of effective and efficient Accountability the purpose of the research is toknow the accountability the management of the budget revenue of regional expenditure in infrastructure developmentThis research uses descriptive approach that is qualitative. The focus in research is the accountability of the managementof budget revenues and expenditures in the area of infrastructure development area in North Halmahera Regency. Datacollection was done through the study of librarianship, Field Studies, interviews, direct observation (observation). In thecurrent study qualitative analysis method is used.The results showed a GRANT Management Accountability in the area of North Halmahera Regency of honesty and lawhave not been too good, this in view of the still existing of abuse of authority in matters of local development planning. Thencompliance with regulations or legislation are still less well so there was created a governance which is good anyway. Theprocedures used in pushing the course assignments and functions of development planning in the area of North HalmaheraRegency not too good because the supporting tools used have not been too complete. The competence of human resourcesremained a major constraint, so that the implementation of development programs that have not been too kind to result ina goal that has been set yet to be achieved. Still the lack of precision of the policies taken by the Government of NorthHalmahera Regency so in charge policy has not taken too well.Keywords: Accountability, Management Of Budget Revenue And Spending Areas, Infrastructure Development